Pengaruh Struktur Modal dan Keputusan Investasi Terhadap Nilai Perusahaan Melalui Profitabilitas - Andi Primafira Bumandava Eka; Mayasari Mayasari (JRAK: Journal of Accounting Research and Computerized Accounting, 2019)
This research is a study that wants to prove from similar studies before, only this research was conducted on consumer goods industry sector companies listed on the Indonesia Stock Exchange in 2017, which aims to know how the influence and how much the capital structure affects the company's value directly, as well as through the interfening variable profitability in making investment decisions towards the value of the company .. By using quantitative research methods that process secondary data, the magnitude of the influence can be calculated using the SPSS statistical tool with path analysis. The results of the study illustrate a very strong influence on the significance level of 92.7% on factors that influence company values ​​such as capital structure, and investment decisions through profitability. The investment decision is partially fakroe which has a unidirectional positive relationship of 0.682 to the firm value. While the capital structure and profitability are not so significant separately, although the combined effect of capital structure on firm value through profitability is 0, 487 and investment decisions on firm value through profitability are 0.541. This research is expected to provide an overview, analysis and prediction of investment decisions that will be taken by investors, both institutional investors and individual investors in consumer goods companies in order to increase the value of the company for sustainable business.